KERJASAMA INDONESIA – MALAYSIA DALAM PENANGGULANGAN KEJAHATAN LINGKUNGAN: STUDI KASUS KABUT ASAP RIAU PERIODE 2008-2013 - Fiani, Putri; Utomo, Tri Cahyo; Pattipeilohy, Shary Charlotte (Journal of International Relations, 2015)
Haze pollution in Riau, Indonesia is an annual problem that should be dealtby Indonesia and Malaysia Governments. Haze pollution is a form oftransnational crime because it has been polluting the environment ofMalaysia. Riau haze pollution coming from forest fires and land adverselyaffecting the entire important aspects. The seriousness of the problem of hazepollution in Riau, need some immediate prevention attempts taken byIndonesia and Malaysia. Indonesia established bilateral cooperation withMalaysia to address this issue because Malaysia is the one that received themost severe negative impact of the haze. The results of the bilateralcooperation is an agreement in the form of a Memorandum of Understanding(MoU) between Indonesia and Malaysia for the prevention of forest fire andhaze in Riau. MoU between the two countries was signed in 2008 andlegitimate until 2013. However, the conditions in Riau due to haze pollution,is getting worse in 2013 which led to the smog disaster. Question problemthat arises is how the implementation of the cooperation between Indonesiaand Malaysia in response to the case of haze in Riau during 2008-2013. Thepurpose of research to describe and analyze the situation in Riau due to haze,haze reduction, and the implementation of cooperation between Indonesiaand Malaysia during the period 2008-2013. In answer to the problems andobjectives of the research carried out by using the theory of internationalcooperation, transnational crime theory, and the theory of environmentalcrimes in the paradigm of liberalism. This research is using a qualitativemethod with the type of descriptive-analytical by using literature reviews andinterviews research technique. The finding of this research is theimplementation of the cooperation between Indonesia and Malaysia has notgiven an effective and optimal results due to it’s lack of time, location, andlaw enforcement as well as human resources problems in Indonesia.